Seeing, Judging And…Acting! Improving Health Perception and Meaningful Occupational Participation in Older Spanish Adults - Rodríguez-Bailón, María; Pulido-Navarro, María José; Bravo-Quirós, Ana; Alberto-Cantizano, María José; Rubio-Fernández, Vanesa; Fernández-Solano, Ana Judit (Taylor & Francis, 2016)
Occupational therapy programs have been developed in order to promote health in older adults. However, no published studies have yet been identified for the Spanish population. This study explores the benefits of an occupational therapy health promotion program called EnvejeHaciendo (AgeDoing). The study was conducted with 15 elderly Spanish adults, examining health perception and meaningful occupational participation using the Model of Human Occupation, as well as the pedagogical methodology See, Judge, Act. The results showed an increase in the perception of health with reference to social functioning and the number of roles in which the participants wanted to get involved in the future. The participants changed their own negative perception of elderly people, they adapted to the changes provoked by aging, and they got involved in meaningful activities such as physical exercise or social activities. This program allowed participants to engage in meaningful occupations with other people and to increase perceived health status through raising awareness of difficulties.
Keywords: Gerontología; Promoción de la salud; Terapia ocupacional; Elderly; Health promotion; Model of Human Occupation; Occupational engagement